DISTRIBUSI PENDAPATAN RUMAHTANGGA PETANI KARET EKS UPP TCSDP DAN SWADAYA DI DESA BINA BARU KECAMATAN KAMPAR KIRI TENGAH KABUPATEN KAMPAR - Agus Ferianto Manik; Eliza ' '; Shorea ' Khaswarina (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2016)
This study aimed to analyze the sources and structure of household income, the distribution of household income, comparing incomes between ex UPP TCSDP farmers and independent smallholders in Bina Baru Village Kampar Kiri Tengah District Kampar Regency. This study used a sample of 30 farmers ex UPP TCSDP and 30 independent smallholders using disproportionate random sampling. The analysis showed that the total average household income of farmers amounted Rp.29.352.760 ex UPP TCSDP farmersper year and independent smallholders household income by Rp.39.855.606 per year originating from agriculture and non-agricultural sector. Figures Gini Ratio Index ex UPP rubber farmer households 0.28 and independent smallholders 0.29 indicates low inequality and Lorenz curve approaches the diagonal line. T-test showed farm household incomes rubber ex UPP TCSDP significantly different from independent smallholdersfarmer household income Keyword : Rubber, Distribution, Structure, Household Income